Effects of Screen Time on Brain Health Studies on The Impact of Digitization on Cognitive Function - Hasnidar Hasnidar; Olyvia Rosalia (Oshada, 2025)
The rapid advancement of digital technology has transformed daily life, increasing the time individuals spend interacting with digital devices, known as screen time. This study investigates the impact of screen time duration on cognitive functions, focusing on memory, attention, and executive function. Using a quantitative explanatory research design, data were collected from 150 participants aged 15 to 40 through standardized cognitive assessments and self-reported questionnaires measuring screen time, sleep quality, physical activity, and digital content type. The results indicate a significant negative relationship between prolonged screen time and cognitive performance, moderated by factors such as sleep quality and age. Passive digital consumption was more strongly associated with cognitive decline compared to active, educational use. These findings highlight the importance of managing screen time to preserve cognitive health and inform strategies for healthier digital habits. This research contributes to the understanding of digitalization’s neuropsychological effects and supports the development of guidelines for balanced technology use.